Implementing Brownâ€™s Teaching Principles on the Training of English for General Speaking Purpose for School Teachers and Staff - Haryadi S; Baiq Sumarni; Imansyah Imansyah; Heri Hidayatullah; K. Dedy Sandiarsa S (Jurnal Pengabdian UNDIKMA, 2021)
This community service aims to help secondary school teachers to learn and improve their English, speaking skill in particular, The community service team will collaborate to conduct 20 class meetings at the respective school. The participants are all school teachers, headmaster, and appointed school staff. This paper informs the result of Brownâ€™s Teaching Principles in improving speaking skill of school teachers and staff. There were 10 teachers involved, 7 males and 3 females. Their ages range between 24 to 30 years. The community service teamÂ  employed observation to record participantsâ€™ progress. The result shows that before commencing the training, participants were mostly unable to make self-introduction, tell daily activities, show directions, and make general exchange. At the end of the program, the participants were able to speak in English in the area of making self-introduction, telling about their daily activities, and making general daily exchange. They were also capable of showing people direction and ask and answer Yes/No question. The speaking zone also developed from â€œin-classroom only areaâ€ to teachersâ€™ room and was planned to expand into the whole area of the school. This policy will be made for teachers first. Students will be advised to use English at school at the initial stage. The school plan to implement English speaking policy for students soon in the right time in the near future.